Global logistics new directions in supply chain management - Waters, C. D. J. 1949- (Kogan Page Ltd., 2007)
The field of logistics is developing at a remarkable pace and its role is now integral to the long term plans of almost all businesses. Communications and IT are offering ever more opportunities; world trade is growing; new markets are developing; yet at the same time there is increasing concern for the environment. The world of logistics is constantly evolving in response to these changes. In the same way, the fifth edition of this established book has evolved to represent the current trends, best practice and latest thinking on global logistics. It serves as a forum allowing the contributors.